DA ESCOLA NO QUILOMBO À ESCOLA DO QUILOMBO: as propostas pedagógicas como possibilidade de diversificar o currículo das escolas quilombolas de Ensino Fundamental no município de Bequimão (MA). - GONÇALVES, Dinalva Pereira (2019)
This paper was written thus a pedagogical research realized through scholar framework support of Programa de Pós-Graduação em Gestão de Ensino da Educação Básica - PPGEEB (Postgraduate Program in Management of Basic Education) from Universidade Federal do Maranhão (Federal University of Maranhão). It traces the development of a study about the role of the “schooling” in quilombola context communities (ethnical comunnities composed by black people during the colonial period in Brazil and after slavery) and it has by objective to construct a specific pedagogical proposal for the diversified part of the curriculum of the quilombola schools in the municipal network of the city of Bequimão, localizated in the northeast region on Brazil, in the state of Maranhão. This proposal was materialized in two Pedagogical Workshops composed of 10 themes that deal with ethnic-racial issues and interest areas of the studied communities, considering their socio-cultural reality and contributing to their cultural valorization and affirmation of ethnical identity. In methodological description, Participative Research is presented as the research gender chosen in order to construct this paper, since this kind of research is developed from the interaction between the researcher and the researched object, in the service of a political-pedagogical work focused on the needs of these historically disadvantaged social groups, in an attempt to intervene in their realities. As a bibliographical reference, it presents excerpts from the legislation pertinent to educational policies for ethnic-racial relations and conceptions of authors such as Albuquerque (2006), Costa (1998; 1999), Fiabani (2005; 2008; 2009), Domingues (2005), Mille (2016), Loss (2014) Melo (2012), Moreira and Candau (2008), Santomé (1995, 2013), Silva Filho (2012), among others. The present work is organized in five sections: the first one is an introductory text with general information about the investigative path; the second one describes the process of formation of quilombola communities in Brazil and Maranhão; the third part presents a discussion about the importance of the achievement of educational policies for black populations and the rights of quilombolas communities to a differentiated schoolling, as well as an analysis of the implications of the school curriculum as a tool of resistance for historical renegade peoples; the fourth section deals with the importance of adopting a specific curricular proposal for the diversified part of the curriculum of quilombola schools as a stimulator of the ethnic affirmation of their students, as well as the detailed methodology applied, the description of the process of elaboration of the final product of the research and the stages of intervention in the studied reality. This study concluded that teachers from Quilombola schools in Bequimão face difficulties regarding the implementation of Brazilian Law 10.639 / 2003 and the National Curricular Guidelines for Quilombola School Education, lacking continuous training and pedagogical support more directed to the specificities of this modality of education. In this way, this research intervened in the reality studied in two ways: the first one beyond the realization of a training event specifically directed to teachers, managers, pedagogical coordinators and community leaders; and the second one with the production of a teaching support material, to be worked in the diversified part of the curriculum, composed of several workshops with ethnic-racial themes and community interest, which we intend that it can be able to help in school practices and contribute significantly to the valorization and evidence of the local Quilombola communities culture.